Identifikasi Tipe Stomata Pada Bebarapa Jenis Tumbuhan Dikotil Dan Monokotil: Identifikasi Tipe Stomata Pada Bebarapa Jenis Tumbuhan Dikotil Dan Monokotil - -, Ridwan; Hasidu, La Ode Abdul; Rumakefing, Hartina (Jurnal Sains dan Pendidikan Biologi, 2022)
Stomata are clefts of the epidermis, each lined by two guard cells. In Greek, stoma means "mouth", and the term is often used only for the stomatal pore. Stomta has long been the object of study of morphology, anatomy and physiology. In general, several technical terms are known, such as stoma, stomata complex, neighboring cells and daughter cells. In general, several technical terms have been known, such as stoma, stomata complex, neighboring cells and daughter cells. The term has been used in different meanings by groups of botanical researchers. This study was conducted to determine the type of stomata in several types of dicotyledonous and monocot plants. The study used a qualitative descriptive method to describe and describe the type of stomata in several types of dicotyledonous plants and monocotyledonous plants. The object of this research uses the abaxil leaf of several types of plants including dicotyledonous plants which include soursop (Annona muricata), mango (Mangifera indica), noni (Morinda citrifolia), breadfruit (Artocarpus altilis), and monocot plants which include: palm leaves, banana leaves, papaya leaves (Carica papaya) and turmeric leaves (Curcuma longa). The research was carried out through several stages, namely the preparation of leaf samples, making leaf preparations, observing under a microscope, documenting and describing the forms of stomata. The results showed that dicot and monocot plants have different types of stomata. Several types of plants also have the same type of stomata. Soursop (Annona muricata) has Paracytic stomata type; Mango (Mangifera indica) has anomocytic stomata type; Noni (Morinda citrifolia) has Paracytic stomata type; Breadfruit (Artocarpus altilis) has Actinocytic stomata type; The palm (Oreodoxa regia) has a Tetracytic stomata type; Banana (Musa sp.) has anomocytic stomata type; Papaya (Carica papaya) has Hemiparacytic stomata type; and Turmeric (Curcuma longa) has Paracytic stomata type.